Marketing Made Simple : A Step-by-Step Story Brand Guide for Any Business - Kishore Babu, M.; Naveen Kumar, B. (Indian Journal of Marketing, 2020)
This is a book review of Marketing Made Simple : A Step-by-Step Story Brand Guide for Any Business by Donald Miller and Dr. J. J. Peterson. Both the authors attempted to elaborate on the process and importance of creation and implementation of a marketing plan consisting of five steps. Further, every step of the proposed marketing plan is discussed at a granular level, which in turn helps the organizations to formulate their own marketing strategy. The role of the sales funnel is explained in detail. The book also explains the different stages of developing a relationship with the customers. The authors establish the need for the creation of brand awareness about the products among customers. The book addresses numerous issues and challenges faced by a majority of the organizations in the context of creating a marketing plan for their products to generate sales. Finally, according to the authors, the prime motto of the organization’s marketing plan should be to focus upon the needs of the customers rather than focusing on creating a brand image.